LEADING INCLUSION: INSTRUCTIONAL LEADERSHIP AND INNOVATION IN SPECIAL NEEDS SCHOOLS - Kristianus Viktor Pantaleon; Fransiskus Sawan; Marselus Ruben Payong (Program Studi PGSD Universitas Flores, 2026)
The implementation of inclusive education in Special Needs Schools (SNS) in Indonesia continues to face enduring challenges, particularly in the contextualization of school-based curricula and developmental strategies. This study investigates the impact of instructional leadership and innovativeness among school principals on their ability to formulate responsive School-Based Curriculum (SBC) and School Development Plans (SDP) within SNS environments. A mixed-methods approach with a contemporaneous triangulation design was employed to collect data via questionnaires from five principals and 77 teachers, in-depth interviews with four principals and four teachers, and document analysis of SBC and SDP materials. Quantitative findings indicated a substantial association between instructional leadership and curricular planning competence (r = 0.377, p < 0.001), as well as between innovativeness and planning competence (r= 0.253, p=0.022). Qualitative findings indicated that although school leaders shown dedication to instructional leadership and pursued several innovations, these initiatives were frequently disjointed and devoid of institutional backing. Document analysis revealed a discrepancy between policy aims and actual planning practices. The study indicates that successful curriculum development in SNS necessitates robust individual leadership, methodical innovation, and organizational commitment. These findings provide guidance for policy reform, leadership development, and the creation of inclusive educational planning frameworks.